Humourising Covid-19 Pandemic Crisis in Nigeria: A Discourse Study of the Selected Online Memes and Posts - Tunde Ope-Davies (Opeibi); Kofo Adedeji; Olusola Aina (University of Chitral Journal of Linguistics and Literature, 2023)
As the global community attempted to fight COVID-19 and cope with the new reality created by the global pandemic, online and mobile social networks played a key role in this new order. This study expands research on the use of these new media technologies for public health-based civic engagement in Nigeria. The primary aim is to explore the use of humour as a discourse strategy in online posts on the COVID-19 pandemic that were designed to create awareness, educate the public, and promote social and public morality. Using approaches in discourse analysis and humour in combination with Scollon’s (1998) Discourse Mediated Theory (DMT), the study discusses how a combination of texts and images mediated through socio-technical affordances of the online platforms underpin the extrapolation of social meanings conveyed through humorous memes and posts. The data set was extracted from the repository of an ongoing project on the corpus of digital health humanities discourse at the Centre for Digital Humanities, University of Lagos. It consists of posts and messages on the COVID-19 crisis circulated on WhatsApp platforms between February and March 2020.  Using a qualitative interpretive paradigm, the study shows how serious and more profound themes of the pandemic are expressed through creative comical online posts and memes. A major observation is that humour appeal is generally sensitive to the culture of the audience as it draws its persuasive tenor from materials, artifacts, and symbols that the audience can easily relate to. Equally, instances of Scott’s (1990) notion of infra politics are found in some of the memes that satirise political situations and political actors in the country. Thus, weaponising the event-generating and event-driven memes for political ends heightens their functions within this situated socio-discursive milieu.